The confessions of Catherine de Medici : a novel - Gortner, C. W. (Ballantine Books Trade Paperbacks, 2011)
Leaving her native Florence to marry Henry II of France, Catherine de Medici embarks on an unanticipated destiny of religious warfare, thwarted leadership, and psychologically charged royal machinations.